INTRACTABLE PARADOXES OF EVOLUTION - WITH ALL-ENCOMPASSING GAZE OF A NATURAL PHILOSOPHER (Experimental biology, 2021)
Although Darwin was really ahead of his time on many of the most fundamental issues for science, however, if we talk about the true mechanisms of evolution (as, indeed, about the absence of transitional forms), they still remain the object of sharp, incessant discussions. The same applies to such a fashionable philosophical concept as the "universal noosphere": after all, many people now interpret it in different ways (including as quite real material formations that function, however, according to laws that are not yet completely available to us). Only one thing is clear: these laws are the same for both living and ordinary inert matter. And in addition, in recent years, most modern scientists have begun to tend to the conclusion that the emergence and progressive development of living beings is possible only if there is an appropriate program (plan, project).The article is devoted to the core and most controversial problems of biology. Its main idea is to postulate the individual mental and the collective noosphere derived from it as the leading factors of evolution. After all, one way or another, it is with their "interested" participation that any dynamic shifts observed in nature are carried out. That is, useful emotional impressions accumulated in ontogenesis by the mental serve as an information base for improving behavioral reflexes in this particular species. And only with some rare saltations (such as, say, the transformation of scales into feathers or forelegs into wings) can we judge the guiding activity of the higher universal mind. Although we are talking about the residual ("posthumous") uni-sphere, which is terminologically very little related to the generally accepted, and much more familiar to philosophers,"Chardin's". It can be described as a giant biocomputer scattered in space, operating at a slower pace compared to current computers, but still having (through its obedient ubiquitous performers – viruses) so far much more power and influence on the fate of modern world civilizations.